2021
DOI: 10.1149/1945-7111/abdc75
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Humidity on Stainless Steel Pitting in Sea Salt Exposures

Abstract: Ground 304 stainless steel (SS) samples were exposed to sea salt particles at 35 °C and two relative humidity (RH) levels for durations ranging from 1 week to 2 years. For all exposure times, pit number density and total pit volume at 40% RH were observed to be considerably greater than those at 76% RH. Statistical analysis of distributions of pit populations for both RH conditions showed that pit number density and total pit volume increased rapidly at first but slowed as exposure time increased. Cross-hatche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…When all individual pit volume growth is summed to show cumulative volume loss (directly proportional to mass loss) in Fig. 2b, the 4N-Al material had similar trends to other materials under atmospheric corrosion scenarios and constant contaminant environments where the corrosion rate slows over time 41,[60][61][62] . However, in the current study, the early stages of corrosion damage did not show the commonly described power law volume/mass loss relationship with time.…”
Section: Discussionmentioning
confidence: 83%
“…When all individual pit volume growth is summed to show cumulative volume loss (directly proportional to mass loss) in Fig. 2b, the 4N-Al material had similar trends to other materials under atmospheric corrosion scenarios and constant contaminant environments where the corrosion rate slows over time 41,[60][61][62] . However, in the current study, the early stages of corrosion damage did not show the commonly described power law volume/mass loss relationship with time.…”
Section: Discussionmentioning
confidence: 83%
“…At lower RHs, below NaCl deliquescence, crevice corrosion was observed to occur under precipitated NaCl crystals with MgCl 2 deliquesced in solution. Srinivasan et al and Weirich et al, 2,3 observed similar correlations with RH through atmospheric exposure of artificial sea salt droplets. At 76% RH, with NaCl dominated brines, the resulting pits were hemispherical with crystallographic surfaces, whereas at lower RH (∼40% RH), with MgCl 2 dominated brines, irregularly shaped pits, with cross-hatching, and micro-cracking were observed.…”
mentioning
confidence: 68%
“…Specifically, relative humidity (RH) and temperature (T) can control the surface brine composition, chemistry, conductivity, electrolyte distribution and volume, and the subsequent pitting damage. [2][3][4][5][6][7] Recent corrosion studies have attempted to replicate aspects of atmospheric exposures in laboratory settings through droplet exposures under controlled atmospheric conditions. Specifically, Street et al, 5 studied the influence of exposure RH on atmospheric corrosion with MgCl 2 droplets exposed under static RH and T conditions and short time intervals (⩽ 24 hours (h)).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The surface roughness also significantly affected the number of corrosion pits. The effect of humidity on the generation of corrosion pit for 304 stainless steel was investigated under sea-salt environments by Srinivasan et al [13]. It was found that, as the RH decreased from 76% to 40%, the corrosion susceptibility increased gradually.…”
Section: Introductionmentioning
confidence: 99%